Neuro fuzzy determination of optimal parameters of laser directed energy deposition for formation of cladding structures. (October 2022) - Anicic, Obrad; Troha, Sanjin; Milovancevic, Milos; Denic, Nebojsa; Vujovic, Vuk
Highlights: Optimal conditions for directed energy deposition. Manufacturing process of the cladding structures. Laser DED process for formation of cladding structures. Abstract: Laser Directed Energy Deposition (DED) process represent an advanced manufacturing process of the cladding structures. However, the process is very complex due the different processing parameters and there is need to establish an optimization model in order to obtain the undeformed structures. In this article the main aim was to identify the most influential attributes for optimal conditions for the laser DED process for formation of cladding structures. The main goal is to track the cladding width Wc, area of cladding zone Ac, area of fusion zone Amix and flatness ratio S. The purpose of this research is to employ an adaptive neural fuzzy inference system (ANFIS) to classify the different input parameters for the formation of cladding structures. The main advantage of the process is optimization of the formation of cladding structures. The procedure was optimized using ANFIS based on four processing factors. Laser power P, scanning speed V, powder feeding rate F, and lap ratio are the input parameters. The cladding zone Ac is most influenced by the feeding rate F. The scanning speed V has the most impact on the fusion zone Amix area. The laser power P has the greatest impact on the flatness ratio S. The cladding width Wc is most affected by the lap ratio. The study, which also takes into account many input factors at the same time, is thought to be the first on a modest scale and will pique everyone's curiosity.